2015
DOI: 10.1002/chem.201501126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Chemistry of Iminophosphanes

Abstract: Iminophosphanes are a new group of 1,3-P,N-ligands, readily obtainable from secondary phosphanes and nitrilium ions, having a tunable N-donor site by means of varying the imine substituents. These ligands give, in high yields, monodentate gold complexes and bidentate rhodium and iridium complexes. Crystal structures are reported for both the ligands and the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Bis­(imino)­phosphanes can be synthesized from nitrilium triflates and iminophosphanes, which in turn are readily obtained from a nitrilium ion and a phosphane (Scheme ). Recently, we reported on this methodology for the synthesis of 1,3-N,P-ligands and their anions, using a range of phosphane and nitrilium ion substituents, and showed their suitability for transition metal complexation . In addition, we provided a single example of a 1,3,5-N,P,N-ligand ( 5a ; R 1 , R 2 = Ph), generated from the 1,3-N,P-precursor 3a , on which we expand here.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Bis­(imino)­phosphanes can be synthesized from nitrilium triflates and iminophosphanes, which in turn are readily obtained from a nitrilium ion and a phosphane (Scheme ). Recently, we reported on this methodology for the synthesis of 1,3-N,P-ligands and their anions, using a range of phosphane and nitrilium ion substituents, and showed their suitability for transition metal complexation . In addition, we provided a single example of a 1,3,5-N,P,N-ligand ( 5a ; R 1 , R 2 = Ph), generated from the 1,3-N,P-precursor 3a , on which we expand here.…”
Section: Resultsmentioning
confidence: 95%
“…Rare though are the related bis­(imino)­phosphanes ( D ), in which the imine groups are separated by a phosphorus atom, albeit that dipyridylphosphanes ( E ), having pyridine instead of imine groups, are known N,N- and N,P-bidentate and P-monodentate ligands. ,,, Because of the limited access to bis­(imino)­phosphanes D , which may carry different substituents at the P, N, and C sites, we thought it relevant to explore their scope and limitations. In this study, we extend our recent work on 1,3-P,N-ligands and elaborate on the synthesis of N,P,N-ligands including an efficient one-pot procedure, explore their coordination chemistry, report on their rearrangement to an unprecedented 1,3,5-phosphadiazapentadiene ( F ), and also address their oxidizability.…”
Section: Introductionmentioning
confidence: 93%
“…54 (N-Methyl)(methyl)-1-BF 4 has been shown to react in THF with a lithiated C-methyl imine to generate the BF 2 -adduct of asymmetrically substituted β-diimine 36 in poor yield (Scheme 4f ). 55 Recently, we have shown that 1-OTf can be used as an imine synthon for the high-yield synthesis of iminophosphanes 37, which can function as either anionic phosphaamidinate ligands (for R 3 = H) 24 or as neutral 1,3-P,N-ligands (R 3 , R 4 = Ph, tBu or Cy) 56 for transition metal coordination (Scheme 5).…”
Section: Imine Synthonsmentioning
confidence: 99%
“…Subsequent reaction of the chosen trimethylsilylphosphines with the desired imidoyl chlorides affords the target PCN ligands in high yields . Although 1-phosphanyl methanimines and their coordination chemistry with Au, Rh, and Ir have recently been described, the ligands were prepared using a more-complex, less-flexible synthesis strategy.…”
mentioning
confidence: 99%